Evaluation of the Implementation of Pancasila Values and Human Rights Enforcement in Indonesian Judicial System Through Constitutional Approach - Saragih, Geofani Milthree; Ishwara, Ade Sathya Sanathana; Putra, Rengga Kusuma (Reformasi Hukum, 2024)
This study evaluates the application of Pancasila values and the enforcement of human rights in Indonesia's judicial system through a constitutional approach. Using normative legal research methods, the approach taken includes analysis of legislation, conceptual studies, as well as case studies of a number of relevant Constitutional Court decisions. The results show that the values of Pancasila, particularly the second and fifth precepts, play a fundamental role as the philosophical basis in the application and interpretation of human rights principles in Indonesia. The Constitutional Court has a strategic role in safeguarding the constitution while ensuring the enforcement of human rights through progressive legal interpretation. However, despite these positive steps, challenges such as inconsistencies in lower court decisions and mismatches between the rule of law and the needs of society remain. This research recommends strengthening Pancasila-based legal education, harmonizing legal policies, and increasing the capacity of judges in integrating human rights with social justice principles holistically. The findings confirm that the judicial system, with a strong constitutional approach, can be an effective tool in realizing social justice in accordance with the values of Pancasila and the constitution.